Creational narratives for new housing communities: evidence synthesis. Issue 3 (19th September 2016) - Meads, Geoffrey David; Lees, Amanda; Tapson, Kit
Abstract : Purpose: The purpose of this paper is to report the findings of a rapid evidence synthesis commissioned by the Diocese of Winchester with a remit to provide an empirical basis for church contributions to large housing community developments. It sought to respond to three questions concerning new community developments. These related to risks and causes of failure; learning from past corporate and intermediate tier interventions at diocesan and equivalent levels by religious denominations; and the transferable learning available from developments described in community health and liveability literatures. Design/methodology/approach: The review took a purposive approach to sampling evidence from within academic literature, policy and "think tank" outputs and theological texts. The search was instigated with the use of keywords (including New Settlements, Urban Redevelopment, Diocese, Faith and Community), principally within the SCOPUS, NIHR, PUBMED and Google Scholar databases. A pragmatic snowballing approach to relevant references was then employed. Findings: Segregation and separation were identified as the main risk for new settlements. Connectivity is required between and across neighbours, ensuring communal access to services, transport and recreation. Communal places where people can come together for conversation and social interaction are identified as contributing significantly to healthy communities. Churches have a particular positive contribution to make here, through a focus on inclusion, hospitality and common values, rather than single faith-based, evangelical approaches. Practical implications: The initial effect of the study has been to increase confidence in and awareness of the diocesan contribution. In the longer term the three areas of practice highlighted for enhanced faith-based contributions are those of public communications, community integration and civic leadership. An evidence-based approach appears to be especially significant in facilitating the latter. Originality/value: The importance of "creational narratives" in defining and making explicit the values underpinning new housing communities is identified as a singular source of shared motivation for planning and faith agencies.